Evaluation of Soil Characteristics and Environmental Parameters of Arid-Semi Arid Desert Truffles from Eastern Turkey - Akyüz, Mehmet; Kırbağ, Sevda; Gürhan, Yasemin; Bircan, Burak (Hacettepe Üniversitesi, 2017)
The ecological characteristics of arid-semi arid truffles from Eastern Turkey were investigated. The habitat and climate characters of the collection sites were determined and soil samples from localities were analysed. The light strength, temperature, humidity, air flow and air velocity at the areas were recorded to be 17.7 klux to 303.9 klux, 7.8°C to 24.3°C, 11.9% to 43.2%, 3702.6 ft³/min to 8941.6 ft³/min, and 3.6 km/h to 16.9 km/h, respectively. Environmental parameters match the climatic requirements, which is normal for the region when spring is concerned. The soil samples contained 42.59% to 91.46% sand, 4.49% to 38.43% clay, 4.04% to 25.91% silt, 8.54% to 57.41% silt-clay. The soil types included sandy, sandy-loam, clay-loam, loam-sand, sandy- clay-loam types. The soil examples were understood to have alkaline characteristics and had a lime content. The level of organic material and nitrogen was low, whereas the amounts of phosphorus, potassium and sodium were high. Based on our studies and observations, it is possible to claim that habitat, host plant, climate, and soil types are as important as precipitation for the healthy growth of truffles.

T ürkiye’nin doğusunda kurak-yarı kurak trüflerin ekolojik özellikleri incelenmiştir. Toplama alanlarının habitatı ve iklim özellikleri belirlenmiş ve elde edilen toprak örnekleri analiz edilmiştir. Çalışılan alanların ışık şiddeti, sıcaklık, nem, hava debisi ve hava hızı sırasıyla 17.7-303.9 klux, 7.8-24.3ºC, %11.9-43.2, 3702.6-8941.6 ft3/min ve 3.6-16.9 km/h olarak kaydedilmiştir. Ölçülen çevresel parametreler iklimsel ihtiyaçlarla örtüşmektedir. Ölçümler bölgenin bahar ayı koşulları itibariyle normal düzeydedir. Toprak örnekleri %42.59-91.46 kum, %4.49-38.43 kil, %4.04-25.91 toz, %8.54-57.41 toz-kil ve toprak tipleri ise kumlu, kumlu-balçık, killi-balçık, balçıklı-kum ve kumlu-killi-balçıklı toprak türünü içermektedir. Toprak örneklerinin alkali yapıya sahip olduğu ve kireç içerdiği anlaşılmıştır. Organik madde ve azot oranının düşük olduğu fakat fosfor, potasyum ve sodyum içeriğinin yüksek olduğu görülmüştür. İnceleme ve gözlemlerimize dayanarak kurak, yarı kurak ya da çöl trüflerin sağlıklı yetişmesi için yağış kadar habitat, mikorizal bitki, iklim ve toprak tiplerinin de önemli olduğu söylenebilir
Türkiye’nin Doğusunda Kurak-Yarı Kurak Çöl Trüflerin Toprak Özellikleri ve Çevresel Parametrelerinin Değerlendirmesi